Heparin-Binding Growth-Associated Molecule (Pleiotrophin) Affects Sensory Signaling and Selected Motor Functions in Mouse Model of Anatomically Incomplete Cervical Spinal Cord Injury - Kulesskaya, Natalia; Molotkov, Dmitry; Sliepen, Sonny; Mugantseva, Ekaterina; Garcia Horsman, Arturo; Paveliev, Mikhail; Rauvala, Heikki (Frontiers in Neurology, 2021)
HB-GAM (heparin-binding growth-associated molecule; pleiotrophin) is a neurite outgrowth-promoting secretory protein that lines developing fiber tracts in juvenile CNS (central nervous system). Previously we have shown that HB-GAM reverses the CSPG (chondroitin sulfate proteoglycan) inhibition on neurite outgrowth in culture medium of primary CNS neurons and enhances axon growth through the injured spinal cord in mice demonstrated by two-photon imaging. Here we have started studies on the possible role of HB-GAM in enhancing functional recovery after incomplete spinal cord injury (SCI) using cervical lateral hemisection and hemicontusion mouse models. In vivo imaging of BOLD (blood oxygen-level dependent) signals associated with functional activity in somatosensory cortex was used to assess the sensory functions during vibrotactile hindpaw stimulation. The signal displays an exaggerated response in animals with lateral hemisection that recovers to the level seen in the sham-operated mice by injection of HB-GAM to the trauma site. The effect of HB-GAM treatment on sensory-motor functions was assessed by performance in demanding behavioral tests requiring integration of afferent and efferent signaling with central coordination. Administration of HB-GAM either by direct injection into the trauma site or by intrathecal injection improves the climbing abilities in animals with cervical hemisection and in addition enhances the grip strength in animals with lateral hemicontusion without affecting the spontaneous locomotor activity. Recovery of sensory signaling in sensorimotor cortex by HB-GAM to the level of sham-operated mice may contribute to improvement of skilled locomotion requiring integration of spatiotemporal signals in the somatosensory cortex.